KANDUNGAN SELENIUM DALAM HERBA TERSELEKSI DARI DAERAH VULKANIS DAN AKTIVITAS GLUTATION PEROKSIDASE SERTA PENGARUHNYATERHADAPPENYUSUTAN SELMODEL Saccharomyces cerevisiae JB3505 - Rahaju, Sri Hartin (Research Center for Biology-Indonesian Institute of Sciences, 2009)
An exploration of selenium containing herbs was carried out in the Kerinci -Sumatera, Toraja highland-Sulawesi and Rinjani-Lombok. The herbs were sampled according to their morfofisiological characters and local etnopharmalogical information.The analitical parameters were the selenium and selenomethionine content as measured by AAS and GC respectively, gluthathione peroxidase as measured biochemically dan cell model shrinkage observation to reveal the selenium containing extract effect on celluler development. The result indicates the diversity of both content and functional selenium compounds in the selected herbs.The relatively high selenium content herbs such as A Ilium sativuin 1NHR had hingher gluthathione peroxidase and hence its antioxidant activity.However the relatively lower selenium content of Physalis angulata 33NHR was able to induce more cell model shrinkage. The phenomenon of relation among selenium based selenoamino acid, antioxidant and cell shrinkage potential need to be futher studied on these selected herbs.